On explicit finite difference scheme for Korteweg de Vries equation - Dadang Amir Hamzah (Jurnal Rekayasa Teknologi dan Sains Terapan, 2019)
In this paper we apply a finite difference method to approximate the solution of KdV equation. We implement the scheme to the benchmark problem and compare with the exact solution. The results shows that the numerical solution are agree with the exact solution.